THE PRACTICES OF LITERACY AND LITERACY - Maia de Assis, Felipe (Revista Gênero e Interdisciplinaridade, 2023)
This scientific bibliographical article aims to propose a conceptual and practical panorama between literacy and literacy methods. Therefore, the conditions of practices and uses of these will be considered, in the school context of children in the literacy process and in the daily lives of individuals, that is, the social practices recurrent in people’s daily lives, whether they are literate or not. Based on theorists in the area of ​​education, Abreu, Azevedo, Bettelheim, Cagliari, Frade, Ferreiro, Lopes, Mortatti, Oliveira, Rojo, Soares, among others, it is intended to clarify that literacy is the ability to encode and decode signs linguistic - simple and complex letters, words and alphabetic families, and literacy refers to the expansion of the literacy process and/or continuous and conscious uses of social practices that require writing and reading.